Tariff and non-tariff instruments of OPEC+ trade wars - Yan Zhang; Nazim Hajiyev; Valerii Smirnov (Energy Strategy Reviews, 2021)
Under the influence of economic, technological and political factors, the oil market is prone to constant change, which requires analysis of its developmental trends. The purpose of this article is to do a comprehensive analysis of the impact of OPEC + countries on trade wars in the global oil market. The methodological basis of the study was the method of analysis, monitoring and grouping of subject-thematic materials through a logical sequence. The method of analysis is used to determine the features of world oil market globalization, followed by highlighting the advantages and disadvantages of its impact. The study then used monitoring to analyze the linkage of the generalized oil supply and demand balance over the past decade and the factors that affect the development of the oil market. Finally, the tariff and non-tariff instruments used in the OPEC + trade wars were grouped. It has been revealed that the interaction between the participants of the world oil market increases due to the excess of supply over demand within the global balance. This fact can lead to trade conflicts, including the use of non-tariff measures by OPEC + countries such as: voluntary state restrictions, license requirements, quarantine, quotas. In general, the results of the comprehensive analysis showed that the emergence of trade wars in a globalized oil market is influenced by the interaction of three components: institutional, economic and technological, which are complemented by the information base. However, at present, OPEC + performs the function of stabilizer, which reduces trade conflicts in the world oil market. The results obtained can be used in the development of strategies and methods of regulation of trade conflicts in the world oil market by both OPEC + countries and other countries of the world in the context of foreign policy.